Early surgery for partial tears of the ulnar collateral ligament may be more cost-effective and result in longer playing careers than nonoperative management for high-level baseball pitchers: A decision-analytic Markov model-based analysis - Oeding, J. F., MS; Jurgensmeier, K.; Boos, A. M., BA; Krych, A. J.; Okoroha, K. R.; Moatshe, G.; Camp, C. L. (The American Journal of Sports Medicine, 2024)
Background Nonoperative management versus early reconstruction for partial tears of the medial ulnar collateral ligament (MUCL) remains controversial, with the most common treatment options for partial tears consisting of rest, rehabilitation, platelet-rich plasma (PRP), and/or surgical intervention. However, whether the improved outcomes reported for treatments such as MUCL reconstruction (UCLR) or nonoperative management with a series of PRP injections justifies their increased upfront costs remains unknown.